Interpretative phenomenological analysis as a useful methodology for research on the lived experience of pain. Issue 1 (February 2015) - Smith, Jonathan A; Osborn, Mike
Interpretative phenomenological analysis (IPA) is a qualitative approach which aims to provide detailed examinations of personal lived experience. It produces an account of lived experience in its own terms rather than one prescribed by pre-existing theoretical preconceptions and it recognises that this is an interpretative endeavour as humans are sense-making organisms. It is explicitly idiographic in its commitment to examining the detailed experience of each case in turn, prior to the move to more general claims. IPA is a particularly useful methodology for examining topics which are complex, ambiguous and emotionally laden. Pain is a prime exemplar of such a phenomenon: elusive, involving complex psycho-somatic interactions and difficult to articulate. In addition to the 1998 article, published in this Special Issue, two further papers are suggested that the interested reader might wish to look out for.